1981
DOI: 10.1246/bcsj.54.3711
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Highly Dispersed Palladium. II. X-Ray Photoelectron Spectroscopic and Thermal Desorption Studies of the Effects of ZrO2 Added to α-Alumina-supported Palladium

Abstract: The effects of ZrO2 upon the catalytic properties of α-alumina-supported palladium for the hydrogenation of gaseous cyclohexene were studied by means of detailed kinetic analysis, thermal desorption (TD), and X-ray photoelectron spectroscopy (XPS). The catalysts, with ZrO2 added in amounts ranging from 0.1 to 45 in Zr/Pd ratio, were characterized by CO chemisorption and X-ray diffraction. The addition of ZrO2 at the Zr/Pd ratio of 0.5 enhanced the turn-over frequency of the hydrogenation by a factor of 7 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Results of physical and chemical research of catalysts prepared confirmed literature data [6,13,14,[27][28][29][30].…”
Section: 2019supporting
confidence: 81%
“…Results of physical and chemical research of catalysts prepared confirmed literature data [6,13,14,[27][28][29][30].…”
Section: 2019supporting
confidence: 81%
“…Diesel exhaust is a mixture of coarsely dispersed aerosol with a particle size of 0.5-1.0 microns 14,[17][18][19] . The disperse phase of the same mixed aerosol has complex composition and consists of liquid and resinous and solid unburned products.…”
Section: Resultsmentioning
confidence: 99%
“…They are capable of withstanding loads produced during operation under actual operating conditions, as well as meet the requirements of the catalytic converters. Total removal of toxic gases and poisons in the presence of an effective catalyst is possible at the optimum ratio of oxidizing and reducing agents [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%